GREEN SYNTHESIS NANOPARTIKEL ZINC OXIDE (PRO-ZNONP) MENGGUNAKAN EKSTRAK METANOL PROPOLIS DAN POTENSINYA DALAM MENGHAMBAT ENZIM ?-AMILASE DAN ?- GLUKOSIDASE - Ratnasari Plashintania, Dyna
Several studies have shown that zinc oxide (ZnONP) nanoparticles have various health benefits such as anti-diabetic. One of the abilities of ZnONP as an anti-diabetic is by inhibiting the enzymes ?-amylase and ?-glucosidase, and it is known that ZnONP has a higher activity in inhibiting these enzymes when compared to some other metals. However, in synthesizing ZnONP, toxic and environmentally unfriendly chemicals are generally used and the production costs are relatively expensive. Green synthesis is an alternative method that is environmentally friendly and efficient by utilizing organic compounds contained in plants or natural substances to reduce metal ions, one of the natural substances that can be used is propolis. Propolis contains several active compounds such as alkaloids, flavonoids, phenolics, terpenoids, diterpenes, saponins, tannins, proteins and amino acids that can act both as reducing agents, stabilizers and as capping agents in the manufacture of nanoparticles. The purpose of this study was to synthesize and characterize ZnONP using methanol propolis extract using the green synthesis method and to test the inhibitory activity of ?-amylase and ?-glucosidase enzymes in vitro. The green synthesis Pro-ZnONP method was carried out by heating 12.5 mL of propolis extract gradually and when the temperature reached 60 °C, 1.25 g of zinc nitrate hexahydrate (Zn(NO3)2.6H2O) was added to the extract. After that, the mixture was stirred continuously at 60 °C for 1 hour, then incubated without stirring until a white precipitate was formed, and the precipitate was put into a crucible cup. After that the paste was burned in a furnace at a temperature of 700 ° C for 3 hours. Furthermore, the characterization of the formed nanoparticles was carried out using UV-Vis spectrophotometer analysis, High Resolution - Transmission Electron Microscopy (HR-TEM), Fourier transform infrared (FTIR), zeta potential and X-Ray Diffraction (XRD) analysis. Testing of the inhibitory activity of ?-amylase and ?-glucosidase enzymes was carried out in vitro. The results showed that Pro-ZnONP was successfully synthesized through the green synthesis method with a diameter of 30.80-53.11±8.871 nm. These nanoparticles are hexagonal wurzite with an average crystal size of 31.17 ± 6.781 and have a negative charge on the surface area (zeta potential: -67.56±0.77 mV) and have a particle size distribution that is classified as midrange monodisperse with PDI: 0.469± 0.070 and is very stable. The test results showed that Pro-ZnONP had ?-amylase inhibitory activity ranging from 41.00 (20 mg/ml) – 69.52% (100 mg/ml) (IC50 = 43.57 mg/mL), while propolis methanol extract had the ability to lower inhibition ranged from 30.87 (20 mg/ml) – 58.27% (100 mg/ml) (IC50 = 70.54 mg/mL). In addition, Pro-ZnONP showed the ability to inhibit the activity of the -glucosidase enzyme with a percent inhibition of 38.97 (20 mg/ml) – 73.78% (100 mg/ml) and (IC50 = 40.69 mg/ml) . Meanwhile, the inhibition of propolis on the action of the ?-glucosidase enzyme was 29.17 (20 mg/ml) – 55.34% (100 mg/ml) with a value (IC50 = 77.69 mg/ml). Based on the above test, it can be concluded that Pro-ZnONP was successfully produced using the green synthesis method. In addition, Pro-ZNONP has inhibitory activity against ?-amylase and ?-glucosidase enzymes which were tested in vitro.